LEGAL ANALYSIS OF APPOINTMENT OF FORMER CORRUPTION CONCVICTS AS COMMISSIONER OF BUMN (Mimbar Keadilan, 2022)
This study aims to clearly describe the regulation on the appointment of former corruption convicts as commissioners in BUMN and provides an understanding of the legal implications that can occur in the appointment of corruption convicts in BUMN. theoretically this writing is built with a legal perspective on the appointment of former corruption convicts as commissioners of BUMN and is supported by the Theory of Authority, and Review of the principles of good governance. All arguments, facts, and theoretical frameworks in this study are expressed using empirical normative legal research methods. Data obtained and collected through books, journals, papers and papers. Finally, the results of interviews and articles related to the problem. The research method of this case combines elements of normative law which is then added with data or empirical elements. This research is a qualitative research with analytical descriptive nature. The results of this study, namely where the appointment of former corruption convicts as the board of commissioners in a subsidiary of a BUMN has been in accordance with applicable regulations. However, according to Law No. 19 of 2003 article 28 paragraph (1), it is stated that members of the Board of Commissioners are appointed based on integrity considerations, in this case the author assumes that there is a legal loophole that can be used as a legal basis for the appointment of the board of commissioners in BUMN. The integrity requirement as a material requirement is only used as a supporting requirement for the appointment of a commissioner. Meanwhile, integrity is an important requirement that must be carefully considered by the deputy as an assessor of the prospective commissioner to be appointed. Integrity greatly affects the sustainability and application of good corporate governance principles in the scope of SOEs. Fulfillment of integrity is a requirement and element of assessment in which integrity concerns the track record of the prospective commissioner concerned.